Progressive myoclonic epilepsies - Vasquez-Baiocchi, Marco A. J. (2021)
Progressive myoclonus epilepsies (PME) are infrequent neurodegenerative disorders clinically and genetically heterogeneous cause, characterized by action myoclonus, seizures and progressive neurologic disability. They mainly affect children and teenagers. Its early clinical features make the differential diagnosis difficult with other, more frequent neurogenetic diseases such as juvenile myoclonic epilepsy. The majority of genetic mutations that lead to these diseases are known to be autosomal-recessive inheritance, with autosomal-dominant or mitochondrial inheritance being of exceptional frequency. The diagnosis is made when the mutations are identified in a patient with characteristic clinical features (like in the Univerritch-Lundborg disease or North Sea PME). On the other hand, in some cases pathological (vgr., for Lafora body disease or for Myoclonic epilepsy with ragged-red fibers) or specific laboratory test (such as sialic acid in urine for Sialidosis), are more useful. It is important to make as specific a diagnosis as possible because there are some genetically defined therapies for some of these diseases. The management of the seizures in these diseases includes the use of valproic acid as a first-line drug treatment, and other drugs like zonisamide and levetiracetam as second-line. However, the lack of response to antiepileptic drugs is not uncommon. Although the prognosis varies within diseases, it is generally unfavorable and may lead to disability or early death.